Instagram Virtual Network Addiction and Sleep Quality Among Students Pursuing a Speech and Hearing Course - Lancy D’Souza; Mohammad Bagher Negahban (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2019)
Background: Currently the social networking application Instagram has taken higher priority of usage over many other such social networking applications. Objectives: In the present study, an attempt was made to determine the relationship between Instagram addiction and sleep quality of students pursuing a speech and hearing course. Methods: The present study adopted a correlational research design. The sample consisted of 110 students, comprised of 18 male and 92 female students aged between 17 and 25 years old from Mysuru city. Students pursuing a speech and hearing course completed the test for Instagram addiction (TIA) developed by D’Souza, Samyukta and Bivera, and Pittsburgh sleep quality index (PSQI) during September to November, 2018. Test for Instagram addiction measured addiction by considering six factors, including lack of control, disengagement, escapism, health and interpersonal troubles, excessive use, and obsession. The PSQI measured global sleep quality. Pearson’s correlations were employed to find the relationship between dimensions of Instagram addiction and sleep quality. Stepwise multiple regression was employed to find the major predictors of sleep quality by factors of Instagram addiction. Results: The results revealed that among students pursuing speech and hearing selected for the study, only 0.9% were definitely addicts and 14.5% were ‘addicts prone’. The majority of the selected sample (60.9%) had healthy sleep quality. As addiction to Instagram increased, sleep quality of dental students decreased linearly and significantly (r = 0.536). ‘Escapism’ (29.8%) and ‘disengagement’ (2.5%) factors of test for Instagram addiction were found to be the major predictor (32.3%) of sleep quality. Conclusions: It was concluded that Instagram addiction affects sleep quality negatively